Mutation of genes controlling mRNA metabolism and protein synthesis predisposes to neurodevelopmental disorders. (27th November 2015) - Sartor, Francesca; Anderson, Jihan; McCaig, Colin; Miedzybrodzka, Zosia; Müller, Berndt
Abstract : Brain development is a tightly controlled process that depends upon differentiation and function of neurons to allow for the formation of functional neural networks. Mutation of genes encoding structural proteins is well recognized as causal for neurodevelopmental disorders (NDDs). Recent studies have shown that aberrant gene expression can also lead to disorders of neural development. Here we summarize recent evidence implicating in the aetiology of NDDs mutation of factors acting at the level of mRNA splicing, mRNA nuclear export, translation and mRNA degradation. This highlights the importance of these fundamental processes for human health and affords new strategies and targets for therapeutic intervention.